Adjuvant treatment for high‐risk salivary gland malignancies and prognostic stratification based on a 20‐year single institution experience. Issue 4 (7th October 2020) - Onderdonk, Benjamin E.; Vokes, Everett E.; Gwede, Michael; Blair, Elizabeth; Agrawal, Nishant; Haraf, Daniel J.
Abstract: Background and Aim: Retrospective analysis of the utility of adjuvant radiation (RT) or chemoradiation (CRT) and identify prognostic features for patients with high‐risk head and neck salivary gland cancers. Methods: From 1/1997 to 12/2017, 108 patients underwent surgery, and RT (n = 50) or CRT (n = 58) for positive lymph node(s), extracapsular extension, perineural invasion, lymphovascular space invasion, positive/close margin, and/or grade 3 disease. Outcomes were estimated with the Kaplan‐Meier method. Significant predictors identified through regression analyses were incorporated into multivariable regression (MVA). Toxicities were compared using chi‐square. Results: The median follow‐up was 52 months (range: 3‐226). The number of risk factors (RFs) between RT and CRT groups were: 0 to 1 (44% vs 7%), 2 to 3 (48% vs 41%), or 4 to 6 (8% vs 52%), respectively ( P  < .01). On MVA, stage 3 or 4 disease predicted worse outcomes including overall survival (HR 4.55, P = .01). Increasing number of RFs predicted worse disease‐free survival, distant metastasis‐free survival, and overall survival (2‐3 RFs: HR 3.38, P = .03; 4‐6 RFs: HR 5.78, P  < .01), but not locoregional control ( P = .54). So, adjuvant CRT may have provided comparable locoregional control for patients with more adverse features, but the CRT did not translate into improved distant control. There was no difference in acute or late grade 3+ toxicities, or parenteral nutrition ( P = .98, P = .85, and P = .83), respectively. Conclusions: Adjuvant CRT provides adequate locoregional control in patients with more adverse RFs. The absolute number of RFs serves prognostic significance and should be considered in future prospective trials.